Radio‐cephalic fistula recovered with drainage to forearm basilic vein. Issue 4 (10th January 2017) - Norton de Matos, António; Sousa, Clemente Neves; Almeida, Paulo; Teles, Paulo; Loureiro, Luís; Teixeira, Gabriela; Rego, Duarte; Teixeira, Sérgio
Abstract: Dysfunction problems with vascular access are a concern to patients and dialysis units. The vascular surgeon should analyse such dysfunction and perform a careful assessment of the vascular network in order to find new fistula layouts. We introduce and discuss the case of creation of a radio‐cephalic fistula with outflow into the forearm basilic vein through rotation of the forearm basilic vein toward the cephalic vein in the forearm of an 88‐year‐old hemodialysis male patient. This technique enables extending fistula patency and improves cost efficiency.